3D promoter architecture re-organization during iPSC-derived neuronal cell differentiation implicates target genes for neurodevelopmental disorders. (June 2021) - Su, Chun; Argenziano, Mariana; Lu, Sumei; Pippin, James A.; Pahl, Matthew C.; Leonard, Michelle E.; Cousminer, Diana L.; Johnson, Matthew E.; Lasconi, Chiara; Wells, Andrew D.; Chesi, Alessandra; Grant, Struan F.A.
Highlights: High-resolution atlases of chromatin reorganization during neuronal differentiation. Activity of promoter contacting cis-regulatory elements correlates with expression. Neurodevelopmental disorder-associated variants mapped to distal targets. Putative effector genes are enriched for pathways related to neuronal development. Abstract: Neurodevelopmental disorders are thought to arise from interrupted development of the brain at an early age. Genome-wide association studies (GWAS) have identified hundreds of loci associated with susceptibility to neurodevelopmental disorders; however, which noncoding variants regulate which genes at these loci is often unclear. To implicate neuronal GWAS effector genes, we performed an integrated analysis of transcriptomics, epigenomics and chromatin conformation changes during the development from Induced pluripotent stem cell–derived neuronal progenitor cells (NPCs) into neurons using a combination of high-resolution promoter-focused Capture-C, ATAC-seq and RNA-seq. We observed that gene expression changes during the NPC-to-neuron transition were highly dependent on both promoter accessibility changes and long-range interactions which connect distal cis-regulatory elements (enhancer or silencers) to developmental-stage-specific genes. These genome-scale promoter-cis-regulatory-element atlases implicated 454 neurodevelopmental disorder-associated, putative causal variants mapping to 600 distal targets. These putative effector genes were significantly enriched for pathways involved in the regulation of neuronal development and chromatin organization, with 27 % expressed in a stage-specific manner. The intersection of open chromatin and chromatin conformation revealed development-stage-specific gene regulatory architectures during neuronal differentiation, providing a rich resource to aid characterization of the genetic and developmental basis of neurodevelopmental disorders.